Pengaruh Kompensasi Finansial dan Non Finansial terhadap Efektivitas Pengelolaan SDN di Kabupaten Kutai Kartanegara Kalimantan Timur - Nur Agus Salim (Publikasi Pendidikan, 2017)
The purpose of this study was to determine the effect of financial and non-financial compensation on the effectiveness of school management. The research method used is quantitative approach. Data collection techniques used questionnaires and data analysis techniques using descriptive and inferential statistics. From result of hypothesis test that there is significant and positive influence between financial and non financial compensation to effectiveness of school management with result of test F = 148.582 and t test = 12.189 with significance value 0,000. The contribution of financial and non-financial compensation to effectiveness variable of school management is 0,347 which can be interpreted that 34,7% variance of school management effectivity can be influenced by financial and non financial compensation variable and the rest is influenced by other variable not examined in this research. Based on these results it can be concluded that the better the financial and non-financial compensation then the better the effectiveness of primary schools in Kutai Kartanegara.